"A cardinal renewal of the process of teaching schoolchildren in the lessons of a foreign (English) language". - Sereda I. N. (Society and Science: Future Development, 2023)
The article considers the reconstruction of the process of teaching schoolchildren in English lessons in accordance with the Federal State Educational Standard of the new generation.
Keywords: деятельностный подход; самостоятельность; партнерство; partnership; учебная задача; activity approach; личность ребенка; autonomy; personality of the child; learning task